ANALISIS KEMAMPUAN MENGGAMBAR IMAJINATIF SISWA KELAS II SD NEGERI 018 UJUNGBATU - Cici Cahyani; Zariul Antosa; Eddy Noviana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the ability of second-grade students of SD Negeri 018 Ujungbatu in imaginative drawing. This research was quantitative research with a descriptive method. This study started from August 2020 to February 2021. The subjects of this research were 12 second-grade students of SD Negeri 018 Ujungbatu, consisting of seven male students and five female students. This research instrument was an imaginative drawing ability assessment rubric. The research data were collected by using a test technique, namely the imaginative drawing ability test. The indicators for imaginative drawing in this study included: (1) preparing drawing equipment; (2) students remembering and describing the atmosphere and objects in the fruit market; (3) students making sketches of pictures by arranging at least two objects on the market, and (4) students coloring the picture objects consistently and neatly. Based on the study results, it was found that the ability of grade II students at SD Negeri 018 Ujungbatu in imaginative drawing was quite capable because the average score was 73.96 or in the category of Fairly Able. Thus, it can be concluded that the second-grade students of SD Negeri 018 Ujungbatu are quite capable of imaginative drawing.